2004
DOI: 10.4049/jimmunol.173.1.236
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ CD25+ Regulatory T Cell Repertoire Formation in Response to Varying Expression of a neo-Self-Antigen

Abstract: We have examined the development of self-peptide-specific CD4+CD25+ regulatory T cells in lineages of transgenic mice that express the influenza virus PR8 hemagglutinin (HA) under the control of several different promoters (HA transgenic mice). By mating these lineages with TS1-transgenic mice expressing a TCR that recognizes the major I-Ed-restricted determinant from HA (site 1 (S1)), we show that S1-specific T cells undergo selection to become CD4+CD25+ regulatory T cells in each of the lineages, although in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 49 publications
8
52
1
Order By: Relevance
“…The precommitment/selection model is consistent with previous data where an increase in CD4 ϩ CD25 ϩ T reg cells was observed under conditions of exposure to agonist self-peptide (11,13,14,54). Jordan et al (11) showed that coexpression of a Tg TCR with its cognate peptide results in loss or decrease of the CD4 ϩ CD25 Ϫ T cell population, whereas there is an increase in CD4 ϩ CD25 ϩ T reg cells at the same time.…”
Section: Precommitment/selection Modelsupporting
confidence: 80%
See 1 more Smart Citation
“…The precommitment/selection model is consistent with previous data where an increase in CD4 ϩ CD25 ϩ T reg cells was observed under conditions of exposure to agonist self-peptide (11,13,14,54). Jordan et al (11) showed that coexpression of a Tg TCR with its cognate peptide results in loss or decrease of the CD4 ϩ CD25 Ϫ T cell population, whereas there is an increase in CD4 ϩ CD25 ϩ T reg cells at the same time.…”
Section: Precommitment/selection Modelsupporting
confidence: 80%
“…In a recent report, this study was extended by demonstrating that radioresistant stromal cells, expressing the cognate peptide, are capable of mediating both deletion as well as selection of CD4 ϩ CD25 ϩ T reg cells. Moreover, the authors show that populations of CD4 ϩ CD25 ϩ T reg cells and clonally related CD4 ϩ CD25 Ϫ T cells are generated in the same mouse (54). This is in agreement with our model where conditions of heightened deletion result in an increase in CD4 ϩ CD25 ϩ T reg cells, and it is consistent with the hypothesis that a selective enrichment of T reg cells is not directly resulting from heightened TCR signaling during the selection process of the T reg cells but rather an indirect effect due to selective deletion of non-T reg cells and a relative deletion resistance of the T reg cell population.…”
Section: Precommitment/selection Modelmentioning
confidence: 99%
“…Our data are the first to show that within the human fetal thymus, Treg branch off from the developmental pathway of conventional T cells during the transition of DP cells from CD27 -to CD27 + . At this point, the exact molecular signals that initiate this lineage decision remain to be determined, but they could possibly be linked to the strength of TCR signaling or the repertoire of self-antigens presented [27][28][29]. Upon exit from the thymus, CD4 + CD25 + Treg enter the circulation as naive, CD45RA + cells.…”
Section: Discussionmentioning
confidence: 99%
“…PevHA, HACII, and TS1 mice have been previously described (19,31,32) and were backcrossed to BALB/c mice (Harlan Sprague Dawley) at least 10 generations before use in these experiments. All mice were maintained under specific pathogen-free conditions using sterile microisolators at The Wistar Institute Animal Facility.…”
Section: Micementioning
confidence: 99%